Projection in Future Drought Hazard of South Korea Based on RCP Climate Change Scenario 8.5 Using SPEI - Byung Sik Kim; In Gi Chang; Jang Hyun Sung; Hae Jin Han (Advances in Meteorology)
The Standardized Precipitation Evapotranspiration Index (SPEI) analysis was conducted using monthly precipitation data and temperature data on a 12.5 km × 12.5 km resolution based on a Representative Concentration Pathways (RCP) 8.5 climate change scenario, and the characteristics of drought were identified by the threshold. In addition, the changes in drought severity and intensity were projected using the threshold based on the run-length concept and frequency analysis. As a result of the analysis, the probability density function of the total drought and maximum drought intensity moved the upper tail for the upcoming years, and the average drought intensity was also projected to become stronger in the future than in the present to the right side. Through this, it could be projected that the drought scale and frequency and the drought intensity will become severer over South Korea because of future climate change.